Creating a context for campus sustainability through teaching and learning: The case of open, distance and e-learning. Issue 3 (19th June 2019) - Pretorius, Rudi Wessel; Anderson, Ryan; Khotoo, Anisa; Pienaar, Richelle
Abstract : Purpose: This paper aims to reflect on approaches through which open, distance and e-learning (ODeL) students can use their local environments for assessments and explores how this shapes their conceptualisations of "university" and "campus". Key issues and lessons learnt are covered, thus providing pointers for implementation of the type of assessment approaches that are presented. Design/methodology/approach: Using three undergraduate sustainability-related modules in the Department of Geography, University of South Africa (Unisa), the lecturers' reflections on the real-world sustainability learning experiences of students in these modules (2015-2018) have been cross-correlated and compared to present an integrated picture of emerging best practice. Findings: The use of real-world, place-based applications, which form a central theme in the assessment strategy for all three modules, allows students to deal hands-on with sustainability issues, establishes a connection between ODeL students and the university and presents an opportunity to engage these students in real-world sustainability learning despite not being on campus. Research limitations/implications: The case study format and qualitative, reflective methodology present limitations, while specifically focusing on ODeL and the final phase of undergraduate studies. Despite these limitations, the lessons learnt can be of value to universities currently transferring to online offerings, with possible impacts for sustainability learning. Originality/value: This paper addresses misconceptions on the role of ODeL in transforming to sustainability. The criticism that ODeL is suitable for primarily theoretical training is countered by evidence that appropriately structured assessments requiring ODeL students to engage with real-world issues in their local environments, can provide valuable sustainability learning experiences.